Real success without a real job - "Zelinski, Ernie J." (New Delhi, 2008)
Career success is much more than having a real job and earning a decent income. Real career success is truly enjoying what you do for a living and having the personal freedom to perform your work virtually any time you want. This one of a kind guide challenge and inspires you to: Create your own dream job or operate an unconventional business, Find your own important mission, true calling or passionate pursuit with which you can make a great living, Gain courage to escape the corporate world so that you don't have to spend the rest of your life trapped in a cubicle, Be creative and have fun in your work, Restructure your life so that it has meaning, direction and joy, Take charge of your physical, emotional, financial and spiritual well-being, Experience true personal freedom in all areas of your life, Above all, get the most out of your life personally and professionally.
Keywords: Success